The role of advanced glycation end products (AGEs) and the receptor for AGEs (RAGE) in hypertrophic obstructive cardiomyopathy - Shengxu Li; Xuanye Bi; Quanxu An; Yuhang Li; Yazhe Tang (PLoS ONE, 2025)
Background Advanced glycation end products(AGEs)/RAGE(receptor for AGEs) play divergent roles in cardiovascular disease. Our study is to evaluate the correlation between AGEs/RAGE in circulation (soluble AGEs/RAGE, sAGEs/sRAGE) and in myocardium (mAGEs/mRAGE), and to explore their relationship with cardiac function and prognostic value in hypertrophic obstructive cardiomyopathy (HOCM). Methods 78 HOCM patients under septal myectomy were recruited. The soluble and myocardial AGEs/RAGE levels were determined by a commercial available ELISA kit at the time of baseline examination. Strain analysis in HOCM patients derived from cardiac magnetic resonance feature tracking, including global/septal radial strains (GRS/SRS), circumferential strains(GCS/SCS), and longitudinal strains(GLS/SLS). Histological fibrosis was assessed through masson’s staining as collagen volume fraction (CVF). All patients were followed up for a composite endpoint for a median duration of 3.8 years. Results sAGEs/sRAGE were higher in HOCM patients than healthy controls(p = 0.025; p = 0.028). Log sRAGE was correlated with log mRAGE(r = 0.739, p < 0.01), CVF(r = −0.411, p < 0.01), GRS (r = 0.412, p < 0.01), GCS(r = 0.463, p < 0.01). Log mRAGE also showed a correlation with CVF(r = −0.439, p = 0.003), SRS (r = 0.4, p = 0.013) and SCS (r = 0.362, p = 0.03). Log mAGEs was correlated with log mRAGE(r = 0.376, p = 0.012). Multivariate COX analysis revealed that log sRAGE was a significant predictor for the occurrence of adverse events in HOCM patients(HR, 0.013; 95% CI, 0.001–0.313; p = 0.007). Conclusions Circulating RAGE appears to act as a protective biomarker, as it is associated with better prognosis after septal myectomy, reducing fibrosis and improving cardiac function in HOCM patients. It is plausible that higher circulating RAGE levels may be derived from higher expression levels in the myocardium.